2022
DOI: 10.1111/jocd.14839
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of a day/night dual‐antioxidant serum on skin: A randomized, regimen‐controlled study in Chinese women exposed to air pollution

Abstract: Background Chronic exposure to air pollution can negatively affect skin health. Aims To assess the efficacy of the LUMIVIVE® System (LVS), a skincare system consisting of individual day and night serums, in Chinese women exposed to air pollution. Patients/Methods In this single‐center, vehicle‐controlled study, eligible females (mean age, 49.02 years) were randomized 1:1 to treatment group (LVS plus basic moisturizer) or control group (basic moisturizer). Skin color, sebum content, barrier function, elasticity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Employing methods from randomized controlled trials to blinded assessments ensures the reliability of results, advancing the scientific foundation for skincare development and validating efficacy claims. 19,[31][32][33][34] This study highlights the antioxidant potential of combining Andrographis paniculata, Syzygium aromaticum, and Pogostemon cablin in anti-aging products. However, due to the variety of free © 2024 the authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing methods from randomized controlled trials to blinded assessments ensures the reliability of results, advancing the scientific foundation for skincare development and validating efficacy claims. 19,[31][32][33][34] This study highlights the antioxidant potential of combining Andrographis paniculata, Syzygium aromaticum, and Pogostemon cablin in anti-aging products. However, due to the variety of free © 2024 the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Integrated into skincare products, such as facial wash, moisturizer, and serum, these extracts aim to counteract skin aging by acting as antioxidant. Highlighting the importance of product-based research, Liu et al, 19 demonstrated that the LUMIVIVE® System (LVS), a day and night serum duo with antioxidants and peptides, alongside a basic moisturizer, reduced pigmentation, redness, and maintained sebum levels, especially in pollution-exposed populations. This study highlights the potential of combining Andrographis paniculata, Syzygium aromaticum, and Pogostemon cablin in antiaging cosmetics, focusing on the antioxidant activity of developed skincare products such as facial wash, moisturizer, and serum.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, antioxidants from Deschampsia antartica extract and antioxidant serum were evaluated in vivo through direct skin treatment in clinical subjects. 37 , 38 These research models have proven to be robust and useful in elucidating the effects of antioxidants against various pollutants and can thus be adopted in future studies.…”
Section: Discussionmentioning
confidence: 99%